2015
DOI: 10.1590/1414-431x20143962
|View full text |Cite
|
Sign up to set email alerts
|

Sorafenib prevents liver fibrosis in a non-alcoholic steatohepatitis (NASH) rodent model

Abstract: Liver fibrosis occurring as an outcome of non-alcoholic steatohepatitis (NASH) can precede the development of cirrhosis. We investigated the effects of sorafenib in preventing liver fibrosis in a rodent model of NASH. Adult Sprague-Dawley rats were fed a choline-deficient high-fat diet and exposed to diethylnitrosamine for 6 weeks. The NASH group (n=10) received vehicle and the sorafenib group (n=10) received 2.5 mg·kg-1·day-1 by gavage. A control group (n=4) received only standard diet and vehicle. Following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 36 publications
1
22
0
1
Order By: Relevance
“…Sorafenib inhibits receptor kinase phosporilation and its downstream pathways [21,22]. Previous studies had shown that sorafenib inhibits TGF-β Smad signaling and Akt signaling [23][24][25]. Treatment with sorafenib in experimental hepatic fibrosis also showed that extracellular matrix marker such as TIMP-1 could also be decreased [26].…”
Section: Discussionmentioning
confidence: 99%
“…Sorafenib inhibits receptor kinase phosporilation and its downstream pathways [21,22]. Previous studies had shown that sorafenib inhibits TGF-β Smad signaling and Akt signaling [23][24][25]. Treatment with sorafenib in experimental hepatic fibrosis also showed that extracellular matrix marker such as TIMP-1 could also be decreased [26].…”
Section: Discussionmentioning
confidence: 99%
“…The anti-fibrotic effect of sorafenib is clearly demonstrated by numerous experiment studies. In nearly all animal models of liver fibrosis, such as carbon tetrachloride (CCl 4 ), bile duct ligation (BDL), dimethylnitrosamine (DMN), diethylnitrosamine (DEN), or thioacetamide (TAA) induced models, sorafenib exhibits anti-liver fibrosis effects ( Hennenberg et al, 2009 ; Wang et al, 2010 ; Thabut et al, 2011 ; Hong et al, 2013 ; Westra et al, 2014a ; Liu et al, 2015 ; Stefano et al, 2015 ; Table 2 ).…”
Section: Anti-fibrotic Activity Of Multitargeted Tyrosine Kinase Inhimentioning
confidence: 99%
“…The RNA quality and total RNA concentration were performed as reported previously. 10 Samples were kept at –80 °C until processing by quantitative RT-PCR (qRT-PCR).…”
Section: Methodsmentioning
confidence: 99%